(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Positions related parties have become a regular feature and the general business and trade these days as it can enter the facilities in transactions with related parties on terms no enters them is with the parties relationship in normal circumstances, and that he found the funniest people relationship have an effect on the outcome of activity and financial position of the entity and its decisions financial and operational. In order to ensure "transparency" in the financial reports, most accounting around the world standards determines that disclosure of transactions with related parties, it is important to have a local accounting rules these relations as well as the unnecessary disclosure of the nature of these relations and compensation management and mutual operations between Related party balances and menu